Association between methyl donor nutrients’ dietary intake with phenotypic aging among US adults: a cross-sectional study from NHANES 2005–2018 - Yong Li; Da Peng; Zhenyuan Yu; Jiaqi Deng; Lijuan Zhao; Ruoyan Cao (Scientific Reports)
Abstract This study investigates the association between dietary methyl donor nutrients intake and phenotypic aging. This cross-sectional study comprised 27,211 adult participants from the NHANES 2005–2018. The methyl-donor nutritional quality index (MNQI) was calculated by assessing the intake of the seven methyl donor nutrients: protein, folate, choline, riboflavin, vitamin B6, vitamin B12, and zinc. Phenotypic age acceleration (PhenoAge.Accel) was calculated using biochemical markers to assess biological aging. Weighted generalized linear regression models were utilized to assess the associations between MNQI and PhenoAge.Accel, and the impact of different demographic and health characteristics was evaluated through interaction effect tests. After adjusting for various potential confounding factors, a significant negative association was found between MNQI and PhenoAge.Accel (β = − 0.66; 95% CI − 0.91, − 0.40; P < 0.0001), indicating that an increase in MNQI is associated with a slowdown in PhenoAge.Accel. Furthermore, subgroup analysis indicated stronger negatively association between MNQI and PhenoAge.Accel in males (β = − 0.94; 95% CI − 1.36, − 0.52) with significant interactions (P interaction = 0.02). In adult populations, the dietary MNQI is negatively associated with PhenoAge Accel, suggesting that choosing high-quality methyl-donor foods can help develop effective nutritional strategies to enhance healthy longevity.